PENGARUH MENGHAFAL AL-QUR’AN TERHADAP PEMBENTUKAN KARAKTER SANTRI DI PESANTREN - Mawarda Habibah; Noor Amirudin (Fakultas Agama Islam Universitas Muhammadiyah Luwuk, 2023)
The background of this research is the decline in character from year to year, especially students in Islamic boarding schools, while the research conducted by the author obtained data showing that there are some students who have good character. Based on this incident, this study aims to find out whether there is an influence of memorizing the Qur'an on the formation of the character of students at the Ayatur Rahman Islamic Boarding School. This study uses a quantitative approach and is included in the type of inferential research. The subjects in this study were the students of the Ayatur Rahman Gresik Islamic Boarding School with 70 respondents. Because the number of students is less than 100, the research technique uses population techniques and data collection techniques use closed questionnaires. The data analysis technique used simple linear regression with the help of the SPSS software version 23 for Windows. The results of the study are: (1) There is a significant influence between memorizing the Koran on the formation of the character of students at the Ayatur Rahman Gresik Islamic Boarding School, this is shown by the results of R = 0.604, with p = 0.00 <0.05 and is at a moderate level (0.40-0.70). (2) The magnitude of the influence of memorizing the Koran on the formation of the character of students at the Ayatur Rahman Islamic Boarding School is 36.5%, which is indicated by the price of p = 0.00 <0.05 while the remaining 63.5% is in the form of other factors, namely family factors environment, education and society.